Exhibitors’ preference at trade fairs: the case of Zimbabwe International Trade Fair (ZITF) - Shereni, Ngoni Courage; Ncube, Felicity Nokukholwa; Mazhande, Precious (Routledge, 2022)
The success of a trade fair is measured against the quality and quantity of exhibitors in attendance. This research therefore sought to get insights into exhibitors’ preferences that captivate them to attend trade fairs from an African perspective. The objectives of the study were to determine the role that exhibition organizers are expected to play by exhibitors, to establish the nature of benefits sought by exhibitors and to identify service quality preferences by exhibitors. Structured questionnaires were self-administered to 136 exhibitors attending the 2019 edition of the Zimbabwe International Trade Fair. Results revealed that organizers are seen as the link between exhibitors and visitors, hence are responsible for marketing the event so that it lures more exhibitors. An Exploratory Factor Analysis (EFA) done on the benefits sought by exhibitors yielded two factors which are product positioning benefits as well as interaction with key stakeholders. Accessibility of the venue, communication by organizers, boothscapes, exhibition environment and ideal duration of the exhibition are some of the quality issues highlighted as preeminent to exhibitors. A further EFA done on exhibitors’ service quality preference extracted two factors which are logistical arrangements and event atmospherics.